2022
DOI: 10.3389/fonc.2022.1009673
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and outcome of primary sarcomatoid carcinoma of the gallbladder

Abstract: PurposeOur study aims to examine the clinicopathological features, disease progression, management, and outcomes of gallbladder sarcomatoid carcinoma (GBSC) patients.MethodsBetween January 2000 and December 2020, 50 gallbladder cancer (GBC) patients who received surgical treatment and were pathologically verified as GBSC at our institution were enrolled. The clinical and pathological features and survival of these patients were retrospectively reviewed.ResultsThe median overall survival (OS) of GBSC patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Accumulating evidence have suggested that gallbladder adeno-squamous/squamous carcinoma shared a worse prognosis than those with adenocarcinoma 74 79 . Gallbladder mucinous adenocarcinoma 80 and sarcomatoid carcinoma 81 have also been demonstrated to share a worse prognosis than adenocarcinoma. However, there are also pathological subtypes that show a comparable or even more favorable prognosis compared to gallbladder adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence have suggested that gallbladder adeno-squamous/squamous carcinoma shared a worse prognosis than those with adenocarcinoma 74 79 . Gallbladder mucinous adenocarcinoma 80 and sarcomatoid carcinoma 81 have also been demonstrated to share a worse prognosis than adenocarcinoma. However, there are also pathological subtypes that show a comparable or even more favorable prognosis compared to gallbladder adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical study showed positive staining of cytokeratin for the epithelial component (Figure 3A,B) and vimentin for the mesenchymal component (Figure 3C). 1,2 Some tumor cells expressed SMA (Figure 3D). The final histopathological diagnosis was sarcomatoid carcinoma with heterologous differentiation classified as pT3N0M0.…”
Section: Clinical Imagementioning
confidence: 99%